THE EFFECTIVENESS OF NURSE-LED INITIATIVES IN ADDRESSING THE NEEDS OF VULNERABLE AND MARGINALIZED POPULATIONS - Khalid Munahi M Alshahrani, Shujan Shawan Alotaibi, Abdulaziz Fahad Alharbi, Fatemah Mashabb Albogami, Abdullah Hilal Albqami, Maha Mubarak Alamri, Abdullah; Gharamah Alasmari, Abdullah Mofareh Albaqami, Sameer Shalwah M Alosaimi, Meshal Lafi Alotaibi, Azhar Hail Alanazi, Nada Mousa Shubayer (Chelonian Research Foundation, 2022)
The primary cause of mortality globally is cardiovascular diseases (CVD), which disproportionately afflict residents of underprivileged areas. Interventions for behavior modification lead by nurses have high potential to reduce CVD. Unfortunately, little is known about the kind and effect of these interventions in underprivileged areas. The purpose of this review was to close this knowledge gap. The structure for the six-stage scoping review was created by Arksey and O'Malley and revised by Levac et al. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses-Extension for Scoping Reviews (PRISMA-ScR) served as the search protocol's compass. PUBMED/MEDLINE, CINAHL Plus, and Cochrane CENTRAL were the three electronic databases that were searched. The included papers were analyzed using Braun and Clarke's "Thematic Analysis" methodology. Providing sufficient training for nurses, addressing patient access challenges, fostering patient participation, and customizing treatments to target groups were other crucial areas in the promotion of nurse-led behavior change that were recognized. Although there is a great deal of variation in the therapies used and researched to far, the overall results point to the great potential of nurse-led behavior modification interventions for high-risk CVD patients in underprivileged communities. To investigate the particular obstacles and enablers of interventions for certain marginalized populations, further study is required. Keywords: Nurse-led initiatives, cardiovascular diseases, review, nurses, patient access, vulnerable and marginalized populations